Basel II implementation in BRAC Bank Limited: risk based capital adequacy requirement of Bangladesh Bank - Mahmud, Ayaz (BRAC University, 2012)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2011.